Development of Word Root-Based Digital Dictionary for Shorof Mastery - Romyi Morhi; Muhammad Zahid 'Afafarrasyihab Rahimadinullah; Mohammad Ahsanuddin; Irhamni (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2022)
The goal of this research was to explain how to develop a word root-based digital dictionary for shorof mastery to make it easier for language learners in recognizing word root and meaning in the use of dictionaries as well as to find meaning of each or some vocabularies in the text. The research method used in this study was Research and Development, using the ADDIE model which includes five stages, namely (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The subjects were college students and students of Al-Khoirot Islamic Boarding School Malang. The data collection techniques were observation, interview, and questionnaire. This development research data analysis technique used two data analysis techniques, namely qualitative descriptive analysis and quantitative descriptive analysis. The qualitative data is in the form of data identification, data grouping, data presentation and explanation, and conclusion. While the quantitative data is a percentage analysis technique in analyzing quantitative data. The results of this development were in the form of a word root-based digital dictionary for shorof mastery that has six displays, which are preface, instructions for use, dictionary, exercises, references, and developers. The assessment by students and college students reached an average score of 94.7% which is valid category. Hence, it can be concluded that this digital dictionary is feasible to use at any time in learning Arabic and students are able to learn independently wherever they are.